The Poverty of Posthumanism: Evolution and Extinction in Eugene Field's 'Extinct Monsters'. Issue 2 (December 2014) - Doherty, Peter
Abstract : This article interrogates constructions of posthumanism in twenty-first century children's literature criticism and ecocriticism. Focusing on an unpublished manuscript by Eugene Field, it argues that the concept of species extinction undermines the theoretical usefulness of posthumanism. The paper begins by discussing the uses and shortcomings of posthumanism as a critical tool in children's literature. In doing so, it establishes connections with the challenge to the human posed by technology in the twenty-first century and the new understanding of what constitutes the human at the end of the nineteenth century. This paper documents intersections between Field's illustrated poem and contemporary representations of evolution and extinction circulating in popular and scientific natural histories. It is suggested that Field's text is also mediated by the visual traditions which framed contemporary natural history writing. Further, situating Field's poetry for children in a broader tradition of nineteenth-century American poetics committed to authorising the voice of the poet, it asks how this voice is complicated by the new realities of evolution and extinction. Confronted with these new realities, Field's manuscript traces the waning of poetic authority and, it is argued, thereby calls for a new aesthetics of children's literature in the face of extinction.